The impact of herd and overconfidence in Unit Trust investment decision in Malaysia - Naila Aaijaz; Noraani Mustapha; Abdullah Al- Mamun; Tan Boon Pin (International Business Information Management Association, 2013)
The year 2006 was a much remembered year for members of the unit trust industry in Malaysia. Utusan Malaysia 6th and 7th of August 2006 and Chong (2006) reported a loss of RM600 million from Employee Provident Fund (EPF) saving invested in approved unit trust fund. EPF is a compulsory saving for workers in Malaysia, where they are allowed to withdrawal their saving from Account 1 which has more than RM50,000 to invest in approved unit trust fund. With the launching of Private Retirement Scheme (PRS) in July 2012 by our beloved Prime Minister with various tax incentives, investment decision in unit trust fund is utmost important. With this in mind, this paper intends to study how investors’ behavior (herd and overconfidence) impact in investment decision in unit trust fund by using statistical method. It is focused in Peninsular Malaysia; 3 states from the west and 3 states from east Peninsular Malaysia